Customers Perspective with Respect to Payment Apps in Rural Area: A study of selected village of Sonipat - Kumar, Ramesh (PT FORMOSA CENDEKIA GLOBAL, 2024)
This comprehensive study, conducted in a selected village of Sonipat, examines the customers' perspective towards payment apps in a rural setting, in line with India's